Investigation of university students attitudes toward leisure time activities (ardahan university sample) - Fatih Murathan; Talha Murathan; Ali Türker (Türk Spor ve Egzersiz Dergisi, 2019)
The aim of this research is to identify the attitudes of university students towards leisure activities, their levels of participation in activities and the state of adequate opportunities. The population of the study consists of 5200 students having studied in the education year of 2017-2018 and the sample of the study consists of 1057 (538 male, 519 female) volunteer students. In the research “Free Time Attitude Scale” was used as a data collection tool developed by Akgül and Gürbüz (1). According to the findings of the study, the distribution of students ' gender is close to each other. No difference has been found in the attitudes towards leisure activities according to the gender factor (p = 0,402).  It has been found that leisure time attitudes of the students in the Faculty of Engineering and School of Physical Education and Sport higher than the other faculties. In the age factor, the difference has been found only in the behavioral area. While the participants think that their academic GPA effects success positively, no significant difference has been observed in pearson correlation analysis. As a result, it can be said in the research that female students are much more social and positive compared to male students in decision making in terms of leisure time activities.